Implementasi Perilaku “MEGERMET” dan Pelatihan Pertolongan Pertama Keracunan Akut Pestisida pada Perempuan Tani di Desa Semangat - Br Karo, Evi Indriani; Nasution, Diah Lestari; Kaban, Febrina Oktavinola (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
The use of chemical fertilizers (pesticides) is one of the biggest occupational health threats facing by farmer workers, especially women. Improper use of pesticides can have a negative impact on poisoning users. The lack of awareness about the negative effects of chronic diseases caused by exposure to pesticides, lack of information about the risks of using pesticides, resulting in pesticides being often used irresponsibly and inappropriately, both the dosage and practice of using them are inappropriate and unsafe and farmers often do not wear appropriate Personal Protective Equipment (PPE) when using pesticides. This community service aims to improve the health quality of the women farmers in the Semangat village through the implementation of